The Relationship between Phonological Awareness and the Early Detection of Dyslexia (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: The Aim Of The Study Is The Possibility Of Early Detection Of Dyslexia In The Pre-Schooling Period. This Is Done By Analyzing Phonological Awareness And Its Relationship With Reading .To Draw Results ,We Focused On The Scientific Methodology By Preparing An Early Detection Test About Dyslexia .This Was Based On Some Criteria .Each Criterion Contained The Major Phonological Skills That A Child Acquires In This Period .After Applying The Test And Determining The Psychometric Characteristics ,It Was Applied On Children In The Kindergarten Detecting The Cases That Found Difficulties To Respond To The Different Criteria Eliminating All The Disturbances Which Could Be The Cause .We Considered Their Cases From The Kindergarten Till The Third Year Primary School Applying The Reading Test And Drawing The Conclusions Using Spss .We Found Out A Relation Between The Phonological Awareness And The Early Detection Of  Dyslexia .The Spearman Link Coefficient Was About 0,98 .And This Was A Strong Proof That There Was A Relation At 0,01 .This Meant That The More Are There Difficulties In Phonological Awareness Like Rhyming (Rime) In Childhood ,The More There Would Be Difficulties In Reading .Keywords: Early Detection  –Dyslexia –Phonological Awareness.